Peningkatan kualitas lingkungan pemukiman DAS Walanae Kecamatan Sabangparu Kabupaten Wajo - Ishak Ishak (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Walanae Drainage Basin (DAS) in Sabbangparu district of Wajo regency has promising potential with plentiful of fish yields and adequate water sources. However, this condition does not make the people healthier and prosperous. The problems faced by the community in this village are the lack of facilities and technology in processing and utilizing the existing local potential, the quality of clean water is still low, and the slum environment. The main program is the implementation of appropriate technology for water purification systems and processing of fish into ready-to-eat meals, processing various processed fish, which is expected that their quality of life and income will increase. The results are expected to 1) help the community succesfully produce their own processed fish products such as abon and crackers made of fish, (2) fish meatballs, (3) and (4) the availability of a simple water purification system for each family. Thus, it is expected that their quality of life in Sabangparu can increase, including their income.